2010
DOI: 10.3324/haematol.2010.031542
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating macrophages correlate with adverse prognosis and Epstein-Barr virus status in classical Hodgkin's lymphoma

Abstract: BackgroundClassical Hodgkin's lymphoma is characterized by a minority of neoplastic cells surrounded by a heterogeneous background population of non-neoplastic cells including lymphoma-associated macrophages. High levels of expression of both the monocyte/macrophage lineage-associated antigens CD68 and CD163 have been suggested to have pro-tumor effects. The aim of our study was to correlate expression of CD68 and CD163 with the clinico-pathological features and prognosis of a cohort of patients with previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
181
3
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(208 citation statements)
references
References 36 publications
19
181
3
5
Order By: Relevance
“…[10][11][12] However, other studies could not confirm this finding. 13,14 In the present study, we aimed to further characterize the morphologic and immunohistochemical characteristics of HIV-associated Hodgkin lymphoma in comparison to classical Hodgkin lymphoma in non-HIV infected individuals with respect to the composition of the microenvironment and the tumor cell content.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…[10][11][12] However, other studies could not confirm this finding. 13,14 In the present study, we aimed to further characterize the morphologic and immunohistochemical characteristics of HIV-associated Hodgkin lymphoma in comparison to classical Hodgkin lymphoma in non-HIV infected individuals with respect to the composition of the microenvironment and the tumor cell content.…”
mentioning
confidence: 77%
“…A high number of macrophages has been correlated with frequent treatment failure in classical Hodgkin lymphoma. [10][11][12] As the cases in the present series were collected over a long period of time, treatment protocols were heterogeneous and clinical data were not available in all cases. Therefore, the prognostic impact of macrophages in HIV-associated Hodgkin lymphoma should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, cHL is characterized by the presence of a small number of diagnostic Reed-Sternberg cells in a background of bystander reactive cells composed of lym-vestigators, including the present authors, validated the adverse prognostic impact of a high TAM content using immunohistochemical staining for CD68 and CD163 [5][6][7][8][9][10]. TAMs are believed to provide trophic factors that directly accelerate the growth and survival of malignant lymphocytes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[16,[37][38][39][40] Also high CD68 was not found to be independent predictor of primary treatment outcome. However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS. [35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS. [35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports. [19,35,42,44] In the present study, we demonstrated a positive correlation between high CD68+ TAM infiltration and shortened DFS but not DSS.…”
Section: Discussionmentioning
confidence: 99%